Between Idealism and Pragmatism: The Christian Churches’ humanitarian aid to Biafra in and from colonial São Tomé (1967-1970) - Ana Guardião (Revista de História da Sociedade e da Cultura)
During the Nigerian Civil War (1967-70) an airlift and relief projects were negotiated to take place in São Tomé, a Portuguese colony. This article analyses the ways in which the relations between the Portuguese authorities and faith-based voluntary organizations during the Biafran crisis shaped debates about the practice of humanitarian aid. They show how humanitarian and human rights activism shaped the rationale of these organisations in the late 1960s. Moreover, the specificities of the crisis and of the humanitarian response led to reflections on the legitimacy of humanitarian interventions and about the profound intertwinements between the religious, humanitarian and colonial realms at a time when strategies to keep influence in a post-colonial Africa were being devised.